Sanitary and physiological quality of bean seeds treated with Trichoderma spp. - Silva Sarzi, Janaina; Brião Muniz, Marlove Fátima; Rabuske, Jéssica Emilia; da Silva Cruz Couto, Leonardo Fellipe; Strahl, Marisa Ana; da Silva Martello, Laís (Scientia Agraria Paranaensis, 2021)
The presence of pathogens associated in the bean seeds can represent great risks for the development of the crop. Thus, the seed treatment is essential, and the use of antagonistic microorganisms is an effective tool for the control of various pathogens. Therefore, the objective of the study was to evaluate the sanitary and physiological quality of bean seeds treated with spore suspension and culture filtrates of Trichoderma spp. and the effect of the antagonist on the health quality of bean seeds inoculated with Fusarium oxysporum f. sp. phaseoli and Macrophomina phaseolina. For this, five Trichoderma spp. isolates were used in the form of culture filtrate and spore suspension. Sanity tests were carried out, sanity with inoculation of F. oxysporum f. sp. phaseoli and M. phaseolina and germination test by the paper roll incubation method. The spore suspension of Trichoderma spp. obtained the highest percentage of reduction in the incidence of the pathogen in relation to the culture filtrates, in the seed health tests. Culture filtrates of isolates Eco, TR4 and SC were the most promising ones in relation to the analysis of growth and dry mass of seedlings.